STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SMP NEGERI 14 KOTA BENGKULU STUDI KUALITATIF - Khermarina, Khermarina; Rahmansah, Rafel; Khairiyatul Auliya, Siti; Aminah, Siti (Jurnal Ilmu Pendidikan Islam, 2025)
Learning motivation is an important factor in student academic success. This research aims to analyze the strategies used by teachers in increasing students' learning motivation at SMP Negeri 14 Bengkulu City. The research method used is qualitative with a case study approach. Data was collected through observation, in-depth interviews with teachers, and documentation analysis. The research results show that the strategies used include providing positive reinforcement, technology-based learning, personal approaches, and the use of varied learning methods. The conclusion of this research confirms that the teacher's role is very important in increasing student learning motivation through effective and innovative strategies